(untitled) (International Journal of Engineering and Computer Science, 2021)
Research on patents has focused on a myriad of economic and technological problems. However, studies centering patents in the fintech industry remain elusive. Yet patents are a crucial way to display new ideas related to financial markets. This paper reports the analysis of the number and the trend of fintech patents filed and issued in the U.S. from 1972 to 2022, and discusses the consequences of the observed patenting activity on two specific areas related to mortgages: the Housing Price Index and the Affordability Index. The paper also discusses the consequences of the fintech patenting activity on the development of mortgage analytics. It focuses on four components of the development of mortgage analytics: credit assessment, capture of credit risk, design of products, hedging of risk exposure through derivative products. Prior research has shown that patents create positive effects for society. Patents lead to specific innovations. Innovative products lead to economic growth, productivity increases, and job creation. As is the case for technology patents, fintech patents lead to technology-driven financial sector innovations. Financial market innovations become important for financial partners and for the proper functioning of the financial market economy as a whole. Mortgages are the major components of the liabilities of the household economic sector; they hence are a component of the economy. Some market innovations that fintech patents protect concern mortgages or mortgage-related financial products. Those innovations related to the functional characteristics of mortgage products don’t modify the positive effects associated with increasing numbers of patents issued. On the other hand, as has happened in the past with mathematical innovations concerning mortgages, they could potentially generate problems in their use for providers or users if the innovations are just cosmetic.